Quality of life and socio-dental impact among underprivileged brazilian adolescents - Vazquez, Fabiana de Lima; Cortellazzi, Karine Laura; Kaieda, Armando Koichiro; Guerra, Luciane Miranda; Ambrosano, Glaucia Maria Bovi; Tagliaferro, Elaine Pereira da Silva [UNESP]; Mialhe, Fábio Luiz; Meneghim, Marcelo de Castro; Pereira, Antonio Carlos (Springer Nature, 2015)
Purpose to evaluate the influence of clinical variables, individual and contextual characteristics on the quality of life (QL) of underprivileged adolescents in a municipality in the interior of the State of Sa˜o Paulo, Brazil. Methods An analytical cross-sectional study was conducted in Piracicaba, in 2012, with 1,172 adolescents aged 15–19 years, from 21 state schools and 34 Family Health Units. The dependent variables included the socio-dental impact (OIDP) and quality of life (WHOQOL-bref) indices. The dependent variables were classified as individual (DMFT index, CPI Index, age, sex, income, parents’ educational level) and contextual (Social Exclusion Index) variable. The multilevel regression model was estimated by the PROC GLIMMIX (‘‘Generalized Linear ModelsMixed’’) procedure, considering the individuals’ variables as being Level 1 and the contextual variables as being Level 2, and the statistical significance was evaluated at level of significance of 5 %. Results Girls were found to have the worst QL (p\0.000) and greatest OIDP (p = 0.000). There was an increase in OIDP (p\0.001) and diminished QL (p\0.052) with an increase in the periodontal index. This result is marginally significant since the significance probability is marginally greater than 0.05. In turn, there was an increase in QL (p = 0.000) and reduction in OIDP (p\0.000) with an increase in the family income. Adolescents who resided in areas of greatest social exclusion (p = 0.031) and with greater OIDP (p\0.000) presented the worst QL. Conclusion Individual and contextual variables were related to the OIDP and QL in underprivileged Brazilian adolescents.
Keywords: Oral health; Adolescent; Quality of life; Multilevel analysis